2022
DOI: 10.1007/s40964-022-00347-x
|View full text |Cite
|
Sign up to set email alerts
|

Stress-adapted fiber orientation along the principal stress directions for continuous fiber-reinforced material extrusion

Abstract: A proven method to enhance the mechanical properties of additively manufactured plastic parts is the embedding of continuous fibers. Due to its great flexibility, continuous fiber-reinforced material extrusion allows fiber strands to be deposited along optimized paths. Nevertheless, the fibers have so far been embedded in the parts contour-based or on the basis of regular patterns. The outstanding strength and stiffness properties of the fibers in the longitudinal direction cannot be optimally utilized. Theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Different fiber trajectories used in 3D‐printed CFRCs: (A) principal stress trajectories, 69 (B) Tailor woven trajectories, 68 and (C, D) asymmetrical and symmetric fluid flow streamlines 70 …”
Section: Fracture Toughness Improvement Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Different fiber trajectories used in 3D‐printed CFRCs: (A) principal stress trajectories, 69 (B) Tailor woven trajectories, 68 and (C, D) asymmetrical and symmetric fluid flow streamlines 70 …”
Section: Fracture Toughness Improvement Methodsmentioning
confidence: 99%
“…As the fiber direction in the laminates was usually unidirectional and not designed to hinder cracks, the reinforcing performances of continuous fibers were not maximized. To redistribute loads, increase component stiffness, reduce stress concentration, and significantly increase the ultimate strength, different fiber trajectories are proposed, such as woven, principal stress, fluid flow streamlines, and others resulting from numerical optimization processes, [68][69][70] as shown in Figure 14. These fiber trajectory design methods might provide references for improving the fracture toughness of CFRCs.…”
Section: Fiber Path Designmentioning
confidence: 99%
See 1 more Smart Citation
“…58 The direction and distribution designs of continuous fibers could well control the mechanical properties of CNFRCs to meet the customized requirements. 59 In the existing literature, the 3D printing process, fiber surface treatment, and interfacial property optimization were studied to enhance the mechanical performances of CNFRCs. For instance, the selection of the printing parameters showed that decreases in layer height, printing speed, line spacing, and an increase in printing temperature could improve the mechanical properties of CNFRCs within a certain range of parameters.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…CNFRC was designed to achieve high specific strength and customized performance by using continuous fiber to enhance the pure matrix's mechanical performance and control of anisotropy 58 . The direction and distribution designs of continuous fibers could well control the mechanical properties of CNFRCs to meet the customized requirements 59 . In the existing literature, the 3D printing process, fiber surface treatment, and interfacial property optimization were studied to enhance the mechanical performances of CNFRCs.…”
Section: Properties Of 3d Printed Cnfrcsmentioning
confidence: 99%